The preparation and relative bioavailability of an artemisin in self-emulsifying drug delivery system - Sijia Gao; Jingcai Chen; Wanqian Peng; Yang Yang; Yong Yang; Lei Hua; Yanlei Guo; Yunhong Wang; Xiaomei Zhang (Taylor & Francis Group, 2023)
AbstractThe aim of this study is to demonstrate a method for improving the solubility and relative bioavailability of artemisinin using a self-emulsifying drug delivery system (SEDDS). The self-emulsifying drug load, solubility, and emulsifying time were used as the evaluation indices, based on a solubility test and a ternary phase diagram. Optimal Mixture Design in Design-Expert software was used to optimize the prescription of the artemisinin SEDDS. By determining the water distribution coefficient in vitro, combined with the drug concentration-time curve in vivo, a comparison was made of the relative oral bioavailability of the artemisinin SEDDS and the crude drug. The optimal prescription ratio of oleic acid polyethylene glycol glyceride, polyoxyethylene hydrogenated castor oil, and diethylene glycol monoethyl ether in the artemisinin SEDDS was 0.5:0.2:0.3 (wt/wt/wt), with a drug loading capacity of 41.556 mg/g, a solubility of 1.997 mg/mL, and a self-emulsification time of 214 s. The optimal prescription was transparent, slightly yellow, and oil-like. The average loading capacity of artemisinin was 41.912 mg/g, the emulsification time was 231 s, the average particle size was 128.0 nm, the average Zeta potential was -4.29 mV, and the solubility of artemisinin SEDDS in water was 1.997 mg mL-1. It is 33.85 times of the solubility of artemisinin in water, which achieves the purpose of increasing the solubility of artemisinin. The comparison of the oil/water distribution coefficient of the artemisinin SEDDS with that of the crude drug in vitro showed that SEDDS could improve the permeability of artemisinin and promote the absorption in vivo, and the relative bioavailability of the SEDDS agent was at least 1.47 times higher than that of the crude drug. The artemisinin SEDDS could significantly improve the solubility and relative bioavailability of artemisinin.